2014
DOI: 10.1186/s12884-014-0399-6
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and experiences of community members on caring for preterm newborns in rural Mangochi, Malawi: a qualitative study

Abstract: BackgroundThe number of preterm birth is increasing worldwide, especially in low income countries. Malawi has the highest incidence of preterm birth in the world, currently estimated at 18.1 percent. The aim of this study was to explore the perceived causes of preterm birth, care practices for preterm newborn babies and challenges associated with preterm birth among community members in Mangochi District, southern Malawi.MethodsWe conducted 14 focus group discussions with the following groups of participants: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 34 publications
(33 reference statements)
2
33
0
Order By: Relevance
“…The mothers said caring for a preterm baby is physically exhausting and even affects their physical appearance (not able to dress well). Similar findings were also found in a study done in rural Mangochi, Malawi [7] involving mothers, fathers, grandmothers and traditional healers as study participants also reported that caring for preterm newborn was demanding, requiring mothers to be with their babies all the time and this affects their business, farming and household chores.…”
Section: Challenges Of Caring For Preterm Newborns At Homesupporting
confidence: 85%
“…The mothers said caring for a preterm baby is physically exhausting and even affects their physical appearance (not able to dress well). Similar findings were also found in a study done in rural Mangochi, Malawi [7] involving mothers, fathers, grandmothers and traditional healers as study participants also reported that caring for preterm newborn was demanding, requiring mothers to be with their babies all the time and this affects their business, farming and household chores.…”
Section: Challenges Of Caring For Preterm Newborns At Homesupporting
confidence: 85%
“…This was also described in a study on preterm birth in Malawi which reported the high burden of care leading to neglecting business, farming and household chores. 15 Furthermore, health workers complained about a lack of resources to deliver appropriate care of these babies. In the community, fundamental resources such as electricity are lacking and at facility level there are issues with staffing, space and supply of medicine.…”
Section: Lack Of Resourcesmentioning
confidence: 99%
“…14 Previous qualitative studies in Malawi have highlighted that poor community care practices for preterm babies are associated with a lack of knowledge on appropriate care and poverty. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Tolhurst and colleagues provided insight into community perceptions of strategies to prevent preterm births that included prevention and treatment for sexually transmitted infections, avoiding witchcraft, decreasing manual labour, and avoiding violence [ 22 ]. Gondwe and researchers explored perceived causes of preterm birth as well as care practices for preterm babies [ 24 ]. In two hospitals in Malawi, Chisenga and colleagues assessed mothers’ experiences of KMC and determined that awareness, counselling and support were factors increasing KMC uptake whereas long hospital stay, lack of decision-making power, little support, physical discomfort and preference for incubator care were barriers to uptake [ 25 ].…”
mentioning
confidence: 99%